Re-Examining the Role of Hydrogen Peroxide in Bacteriostatic and Bactericidal Activities of Honey - Brudzynski, Katrina; Abubaker, Kamal; Castle, Alan (Frontiers in Microbiology, 2011)
The aim of this study was to critically analyze the effects of hydrogen peroxide on growth and survival of bacterial cells in order to prove or disprove its purported role as a main component responsible for the antibacterial activity of honey. Using the sensitive peroxide/peroxidase assay, broth microdilution assay and DNA degradation assays, the quantitative relationships between the content of H2O2 and honey’s antibacterial activity was established. The results showed that: (A) the average H2O2 content in honey was over 800-fold lower than that observed in disinfectants that kills bacteria on contact. (B) A supplementation of bacterial cultures with H2O2 inhibited E. coli and B. subtilis growth in a concentration–dependent manner, with MIC90 values of 1.25 mM /107cfu ml-1 and 2.5 mM /107cfu ml-1 for E. coli and B. subtilis, respectively. In contrast, the MIC90 of honey against E. coli correlated with honey H2O2 content of 2.5 mM, and growth inhibition of B. subtilis by honey did not correlate with honey H2O2 levels at all. (C) A supplementation of bacterial cultures with H2O2 caused a concentration-dependent degradation of bacterial DNA, with the minimum DNA degrading concentration occurring at 2.5 mM H2O2. DNA degradation by honey occurred at lower than ≤ 2.5 mM concentration of honey H2O2 suggested an enhancing effect of other honey components. (D) Honeys with low H2O2 content were unable to cleave DNA but the addition of H2O2 restored this activity. The DNase-like activity was heat-resistant but catalase-sensitive indicating that H2O2 participated in the oxidative DNA damage. We concluded that the honey H2O2 was involved in oxidative damage causing bacterial growth inhibition and DNA degradation, but these effects were modulated by other honey components.